(untitled) (Journal of the College of Basic Education, 2024)
Zinc oxide has been synthesized by using Chemical spray pyrolysis (CSP) method with different Al concentration (0, 2 and 4) at%. XRD styles reveal that these films are polycrystalline hexagonal wurtzite structure, crystallite size was varied from 13.30 nm to 14.34 nm as Aluminum concentration increase. The AFM images displays uniform, crack free and average particle size was in the range (84.27-72.18) nm. Transmittance spectra have an average about 85%. The bandgap is moved to lower energy as Al doping increase.